P-OGC39 The smell of oesophageal adenocarcinoma: opportunities for tests and treatments. (16th December 2021) - Antonowicz, Stefan; Abbassi-Ghadi, Nima; Bodai, Zsolt; Wiggins, Tom; Markar, Sheraz; Boshier, Piers; Goh, Yan Mei; Adam, Mina; Lu, Haonan; Kudo, Hiromi; Rosini, Francesca; Goldin, Robert; et al.
Abstract: Background: Exhaled breath analysis is a promising approach for oesophageal adenocarcinoma (OAC) early detection. The biomarkers of interest are low molecular weight metabolites including volatile aldehydes. In this translational study we investigated whether these metabolites originated from a tumoral source, and how this might impact the diagnosis and treatment of OAC patients. Methods: The investigative strategy was directed by an unbiased informatics screen of metabolic reprogramming in OAC, and validated using complimentary gene expression assays (n = 638, including controls). Mass spectrometric methods were used to quantify corresponding metabolites and putative source compounds at a tissue level (n = 158), and also in exhaled breath for correlative purposes. Targeted in vitro experiments were performed to demonstrate the cause and effect of the proposed model of metabolic reprogramming in OAC. Results: The unbiased screen and subsequent validation found that reduced aldehyde detoxification is an OAC hallmark. In vitro and in vivo this was associated with endogenous aldehyde accumulation. OAC tissue was generally enriched for volatile aldehydes, including the genotoxins formaldehyde, acetaldehyde, 4-hydroxy-2-nonenal and 2-butenal, and the exhaled biomarker decanal (all P < 0.0001). Decanal concentrations correlated with exhaled concentrations. Considering potential aldehyde sources, the OAC phospholipidome was characterised by desaturated and longer lipid acyls, and these spontaneously generated biomarker aldehyde species at ambient conditions. Enriched genotoxic aldehydes were detectable in base-pairing positions in DNA; this genotoxicity was therapeutically targetable with aldehyde scavengers in vitro. Conclusions: These data support a model for enriched exhaled aldehydes based on increased production from an altered lipid phenotype, and reduced detoxification. Some aldehydes are non-reactive and thus support non-invasive detection. Others react with DNA and increase local genotoxicity; this process is druggable. These findings have implications for OAC early diagnosis and chemoprevention.